The practical and ethical challenges of identifying, accessing and obtaining school canteen transactional data for public health research - Alice Gilmour; Ruth Fairchild (Digital Health)
Objective The purpose of the study was to investigate the feasibility of using existing data to better understand what pupils purchase during the school day and its nutritional quality. This report highlights the ethical challenges experienced in attempting to obtain anonymised school canteen transaction data for public health research. Methods Semi-structured interviews were conducted before a variety of approaches were tried to recruit secondary schools for the study via purposive sampling. Results Barriers encountered included (i) identifying data providers, (ii) identifying data owners, (iii) data sharing and (iv) engaging stakeholders. The approaches taken to mitigate each of these barriers and subsequent ethical issues are summarised so that future researchers are aware of any potential problems. Failure to overcome these blockages meant that the original study had to be curtailed. Conclusions School canteen transactional big data remains an underutilised research resource which has immense potential for understanding adolescents’ dietary choices and nutritional intake across the school day. The inaccessibility of anonymised datasets for public health research and complex political issues surrounding data ownership and sharing must be discussed and effort should be made to circumvent barriers. Establishing the current landscape of school food and drink would be beneficial for policymakers, educators and public health researchers.